2017
DOI: 10.2174/1871520616666160729112854
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling Pathway Inhibitors as Anticancer Drug Candidates

Abstract: Cancer incidence represents an important public health problem worldwide. Nuclear factor kappa B (NF- κB) transcription factor plays a pivotal role in the regulation of genes that control various responses in eukaryotic cells, including proliferation and survival, cytoskeletal remodeling, cellular adhesion and apoptosis. Extensive studies have demonstrated the contribution of NF-κB transcription in the promotion and progression of several hematological malignancies and solid tumors, in which NF-κB constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Moreover, triggering of NF‐κB pathway has already been considered as one of the most significant mechanisms in acquired resistance to chemotherapy and radiotherapy (X. Chen, Kandasamy, & Srivastava, ). These results demonstrate that the inhibition of NF‐κB signaling cascade could be a promising approach to overcome cancer cells resistance to the therapeutic agents (de Castro Barbosa et al, ). Baicalein from Scutellaria baicalensis has been identified as an inhibitor of NF‐κB activation, which suppressed TNF‐α‐induced NF‐κB activation in a dose‐dependent manner.…”
Section: Flavonoids Functional Mechanisms In Leukemia Cellsmentioning
confidence: 71%
“…Moreover, triggering of NF‐κB pathway has already been considered as one of the most significant mechanisms in acquired resistance to chemotherapy and radiotherapy (X. Chen, Kandasamy, & Srivastava, ). These results demonstrate that the inhibition of NF‐κB signaling cascade could be a promising approach to overcome cancer cells resistance to the therapeutic agents (de Castro Barbosa et al, ). Baicalein from Scutellaria baicalensis has been identified as an inhibitor of NF‐κB activation, which suppressed TNF‐α‐induced NF‐κB activation in a dose‐dependent manner.…”
Section: Flavonoids Functional Mechanisms In Leukemia Cellsmentioning
confidence: 71%
“…Interestingly, similar with LY29400, transfection with IkBa vectors could prominently increase the apoptosis proportion induced by CXCR4 shRNA, whereas treatment with IKKa vectors could significantly decrease the cell apoptosis induced by down-regulation of CXCR4 in osteosarcoma cells. The roles of PI3K-AKT and NF-κβ in the regulation of cell growth, proliferation and apoptosis had been extensively investigated [39, 40]. Previous studies revealed that PI3K/AKT/NF-κβ signaling pathway played a vital role in regulating apoptosis in various cancer cells [41-44].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found that NF-κB signaling pathway plays highly important roles in cell proliferation, apoptosis, angiogenesis, in ammation, metastasis, and drug resistance. [23][24][25] A variety of stimuli coalesce on NF-κB activation, which can in turn mediate varied transcriptional programs. 26 In this study, the protein expression of P65, IκBα, and their phosphorylated were detected by western blot.…”
Section: Discussionmentioning
confidence: 99%